Investigating Zakat Institution Performance in Indonesia - Mohammad Bintang Pamuncak; Bayu Taufiq Possumah; Diva Azka Karimah (Center of Strategic Studies (PUSKAS) BAZNAS, 2021)
This study aims to seek the impact of zakat accounting standards (PSAK Shariah No.109) adoption on the financial performance of zakat institutions. This study employed the Difference in Difference (DiD) test and Panel data regression using the data from 5 national scale zakat institutions in Indonesia from 2006 to 2019. This study found a difference in zakat institution performance between the pre and post-adoption of PSAK Shariah No.109, both in the DiD test and Panel data regression model.